2014
DOI: 10.1051/0004-6361/201423536
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the cross-field density structuring in coronal waveguides using the damping of transverse waves

Abstract: Context. Time and spatial damping of transverse magnetohydrodynamic (MHD) kink oscillations is a source of information on the cross-field variation of the plasma density in coronal waveguides. Aims. We show that a probabilistic approach to the problem of determining the density structuring from the observed damping of transverse oscillations enables us to obtain information on the two parameters that characterise the cross-field density profile. Methods. The inference is performed by computing the marginal pos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
(39 reference statements)
1
20
0
Order By: Relevance
“…This curve is based on the general damping profile Eq. (1) and is qualitatively the same as that for the exponential damping regime (dashed curve) alone which has been discussed by previous authors (e.g., Goossens et al 2008;Arregui & Asensio Ramos 2014). A seismological inversion for the density profile parameters (ρ 0 {ρ e , ϵ) based only on the overall damping rate produces a 1D curve in the 2D parameter space due to the problem being ill-posed.…”
Section: Figsupporting
confidence: 82%
See 1 more Smart Citation
“…This curve is based on the general damping profile Eq. (1) and is qualitatively the same as that for the exponential damping regime (dashed curve) alone which has been discussed by previous authors (e.g., Goossens et al 2008;Arregui & Asensio Ramos 2014). A seismological inversion for the density profile parameters (ρ 0 {ρ e , ϵ) based only on the overall damping rate produces a 1D curve in the 2D parameter space due to the problem being ill-posed.…”
Section: Figsupporting
confidence: 82%
“…It has been successfully applied to the seismological inference of coronal loop parameters from the observations of damped kink oscillations (e.g., Arregui et al 2013aArregui & Asensio Ramos 2011). Arregui et al (2013b) describe a version of the seismological inversion technique using the Gaussian and exponential damping regimes based on Bayesian analysis, while Arregui & Asensio Ramos (2014) consider Bayesian analysis of the ill-posed case i.e. the exponential damping regime only.…”
Section: Bayesian Inferencementioning
confidence: 99%
“…Then, the observed values and the theoretical/numerical predictions can be compared by adopting a likelihood of the form (2011), we make use of the basic definition of marginal posteriors, by performing the required integrals over the parameter space. This was first done by Arregui & Asensio Ramos (2014) to infer the density contrast and transverse inhomogeneity length scale from measured damping ratio values. As shown by these authors, although the classic onedimensional curves in the parameter space point to an infinite number of equally valid solutions, not all of them are equally probable.…”
Section: Parameter Inferencementioning
confidence: 99%
“…By assuming a density contrast between the interior of the loop and the external corona, estimates for the transverse inhomogeneity length scale can be obtained. Recent expansions of this idea have considered the Bayesian inversion of both density contrast and transverse inhomogeneity length scale by making use of different damping regimes (Arregui et al 2013) or the computation of their marginal posteriors from observed damping ratios (Arregui & Asensio Ramos 2014). In these studies, the density structuring was arbitrarily prescribed.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we apply this method to observational data from the Atmospheric Imaging Assembly (AIA) of the Solar Dynamics Observatory (SDO). Arregui et al (2013) employed a version of the inversion technique using Bayesian analysis of the two fitted damping times to constrain the loop parameters and errors when the problem is well-posed, while Arregui & Asensio Ramos (2014) considered Bayesian analysis to derive structuring information even for the ill-posed case. Tomczyk et al (2007) discovered ubiquitous transverse velocity perturbations propagating in the corona.…”
Section: Introductionmentioning
confidence: 99%